Qualitative systematic literature review: the experience of being in seclusion for adults with mental health difficulties. Issue 1 (13th March 2017) - Mellow, Amy; Tickle, Anna; Rennoldson, Michael
Abstract : Purpose: The purpose of this paper is to conduct a systematic search of the peer-reviewed qualitative literature investigating the lived experience of seclusion for adults with mental health difficulties, to appraise the quality of the existing literature and synthesise findings. Background: seclusion is a controversial intervention for the short-term management of unsafe behaviours in inpatient mental health services. There has been some sporadic interest in service users' experiences of this. Design/methodology/approach: Systematic literature review and meta-synthesis: data sources – databases MEDLINE, EMBASE, CINAHL and PSYCINFO were searched in July 2015; review methods – the Joanna Briggs Institute's Qualitative Assessment and Review Instrument tools for critical appraisal and data extraction were used to review papers and synthesise findings. Findings: A small number of papers were found, which were of mixed quality. Originality/value: The existing research is limited in both quantity and quality. Although most participants from the existing research described seclusion as mostly negative with the potential for causing iatrogenic harm, some described more positive experiences, often in the context of compassionate interactions with staff.